Serum Exosomal Long Noncoding RNAs ENSG00000258332.1 and LINC00635 for the Diagnosis and Prognosis of Hepatocellular Carcinoma - Xu, Hong; Chen, Yueming; Dong, Xueyan; Wang, Xianjun (Cancer epidemiology, biomarkers & prevention, 2018)
Background: Increasing studies suggest that long noncoding RNAs (lncRNAs) are involved in carcinogenesis of human cancers and might be used as diagnostic biomarkers for cancers. Methods: A total of 301 participants were recruited in the first part of the study, including a hepatocellular carcinoma (HCC) group (n = 60), liver cirrhosis (LC) group (n = 85), chronic hepatitis B (CHB) group (n = 96), and healthy subjects (n = 60). In the second part, we collected 55 HCC patients, 60 CHB patients, and 60 healthy subjects as an independent cohort to validate the ability of the experiential lncRNAs for identifying HCC from CHB. A commercial kit was used to isolate serum exosomes and total RNA. The relative levels of lnRNAs and GAPDH mRNA were measured with TaqMan PCR. Results: The results showed that the levels of ENSG00000258332.1 and LINC00635 in the HCC group were significantly higher than those in the other groups (all P < 0.05). A high ENSG00000258332.1 level in HCC was associated with portal vein tumor emboli, lymph node metastasis, TNM stage, and overall survival (OS; all P < 0.05), and a high LINC00635 level was related to lymph node metastasis, TNM stage, and OS (all P < 0.05). ENSG00000258332.1 discriminated HCC from CHB, gaining an area under the ROC curve (AUC) of 0.719 (cutoff value of 1.345); LINC00635 gained an AUC of 0.750 (cutoff value of 1.690). Furthermore, the AUC for the combination of the 2 lncRNAs and serum AFP (cutoff value of 20 μg/L) was 0.894. The abilities of the 2 lncRNAs for identifying HCC from CHB were validated by an independent cohort. Conclusions: The results suggested that the combination of serum exosomal ENSG00000258332.1, LINC00635, and AFP may be a valuable assay in diagnosis and prognosis of HCC. Impact: Our data will shed light on exosomal lncRNAs as biomarkers for HCC. Cancer Epidemiol Biomarkers Prev; 27(6); 710–6. ©2018 AACR.